Conceptions about mathematics and affectivity towards problem solving in future secondary school mathematics teachers in Peru - Torres Lozano, Alejandro (2025)
The teaching and learning of mathematics in initial teacher training in Peru faces challenges that transcend disciplinary and didactic domains, involving the conceptions that future teachers construct about mathematics and the affective factors associated with problem-solving, which directly influence their pedagogical practice. In this context, the objective of this study was to determine the relationship between conceptions of mathematics and affective attitudes toward problem-solving in future secondary school mathematics teachers. The research was conducted using a quantitative, correlational, and non-experimental design, with a census sample of 128 future teachers. Two Likert-scale questionnaires were used, validated through expert judgment and with adequate reliability indices (α = 0.843 and α = 0.882). Data processing was performed using SPSS version 26. The results show that most participants held moderately favorable conceptions of mathematics and a moderate level of affect toward problem-solving. Furthermore, a moderate and statistically significant positive correlation was identified between these two variables (Rho = 0.466; p < 0.001), indicating that constructivist conceptions are associated with more positive affective dispositions, while rigid and mechanistic views are related to negative affect. Consequently, the importance of promoting training opportunities that foster critical reflection on the beliefs and feelings of future teachers regarding mathematics and problem-solving is highlighted.